2013
DOI: 10.1007/s10517-013-2105-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Anorexigenic Peptide Obestatin on Platelet Aggregation and Osmotic Resistance of Erythrocytes

Abstract: We studied the effects of the anorexigenic peptide obestatin on the coagulation system and blood rheology (by the parameters of platelet aggregation and osmotic resistance of erythrocytes) in vitro and in vivo. Obestatin inhibited in vitro platelet aggregation in the entire dose range and reduced osmotic resistance of erythrocytes in all doses except 300 nmol/kg (obestatin in a dose of 300 nmol/kg had no effect on this parameter). Similar to the results of in vitro experiments, intranasal, intraperitoneal, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Previous studies indicated that obestatin potentially suppressed motility of the gastrointestinal tract [ 25 , 26 , 27 ], regulated the secretion of insulin [ 8 , 21 , 28 , 29 , 30 , 31 ], protected against ischemia-reperfusion injury in various organs [ 22 , 23 , 32 ], inhibited platelet aggregation [ 33 ], prevented H 2 O 2 -induced damage in RGC-5 cells [ 34 ], and had multiple other functions in digestive system [ 35 , 36 , 37 ]. Moreover, obestatin possibly reflected and affected some clinical syndromes [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that obestatin potentially suppressed motility of the gastrointestinal tract [ 25 , 26 , 27 ], regulated the secretion of insulin [ 8 , 21 , 28 , 29 , 30 , 31 ], protected against ischemia-reperfusion injury in various organs [ 22 , 23 , 32 ], inhibited platelet aggregation [ 33 ], prevented H 2 O 2 -induced damage in RGC-5 cells [ 34 ], and had multiple other functions in digestive system [ 35 , 36 , 37 ]. Moreover, obestatin possibly reflected and affected some clinical syndromes [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%